Review paperChemokines and cytokines network in the pathogenesis of the inflammatory skin diseases: atopic dermatitis, psoriasis and skin mastocytosis - Nedoszytko, Bogusław; Sokołowska-Wojdyło, Małgorzata; Ruckemann-Dziurdzińska, Katarzyna; Roszkiewicz, Jadwiga; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Chemokines are signaling peptides which regulate cell trafficking and provide control of the tissue-specific cell homing. In the skin, chemokines are secreted both by the resident cells such as keratinocytes, melanocytes, fibroblasts, dendritic cells and mast cells, as well as by infiltrated cells – lymphocytes, eosinophils, and monocytes. Chemokines, together with cytokines, participate in induction and maintenance of inflammation in the skin and regulate the composition of the cellular infiltrates. Inflammation within the skin is a feature shared by atopic dermatitis and psoriasis, two of the most common dermatoses. Accumulation of activated mast cells in the affected skin is seen both in atopic dermatitis and in psoriasis. This paper presents a concise overview of the current knowledge on the role chemokines have in pathogenesis of atopic dermatitis, psoriasis, and mastocytosis, a disease caused directly by the accumulation and activation of mast cells in the skin.